2016
DOI: 10.1177/0890334416646725
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Promoter Polymorphisms on Cytokine Concentration in Preterm Breast Milk and Subsequent Infant Outcomes

Abstract: Background Breast milk concentrations of immune components are variable between women and interleukin (IL) differences may be associated with infant outcomes. Molecular mechanisms for milk variability remain unknown. Objective The aims were to (1) examine the relationship between maternal IL genotypes and milk concentrations of IL4, IL6, and IL10, (2) describe the trajectories of milk IL change, (3) examine whether maternal IL genotypes predict IL trajectories and/or average weekly IL concentration, and (4) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 74 publications
0
9
1
Order By: Relevance
“…For example, functioning FUT2 (secretors) is often reported as occurring in 80% of Caucasians (Azad et al, 2018) and as low as 11% of Koreans (Park et al, 2005). Allele frequency, which is closely tied to geographic location, contributes to human milk composition, including among mothers who deliver preterm (Baumgartel et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…For example, functioning FUT2 (secretors) is often reported as occurring in 80% of Caucasians (Azad et al, 2018) and as low as 11% of Koreans (Park et al, 2005). Allele frequency, which is closely tied to geographic location, contributes to human milk composition, including among mothers who deliver preterm (Baumgartel et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Maternal genomic DNA was extracted from breast milk whey using Qiagen DNA Extraction Mini Kit (Baumgartel, 2016). We collected genotype data using TaqMan allele discrimination assays to genotype seven functional promoter polymorphisms of IL4 (rs2070874, rs2243250), IL6 (rs1800795, rs1800796), and IL10 (rs1800871, rs1800872, rs1800896).…”
Section: Dna Extraction and Genotypingmentioning
confidence: 99%
“…We sought to describe longitudinal cytokine and CRP MOM profiles, choosing MOM cytokines previously reported in the limited literature to be associated with maternal inflammation. These included IL-1β, IL-1ra, and IL-8 which have been associated with pre-eclampsia (Erbağcı et al, 2005); IL-6 and TNF-α, which may be associated with maternal body mass index (BMI), pre-eclampsia, and infant adiposity (Baumgartel et al, 2016;Erbağcı et al, 2005;Fujimori et al, 2015;Young et al, 2017;Zambruni et al, 2017); anti-inflammatory IL-10, which may correlate with NEC risk (Baumgartel et al, 2016); interferon (INF)-γ, which may upregulate proinflammatory cytokines (Chatterton et al, 2013) and is found in high levels in colostrum (Moles et al, 2015); and CRP, which has been studied in normal and overweight maternal populations (Fujimori et al, 2015(Fujimori et al, , 2017. Finally, we studied free choline, which may negatively correlate with MOM CRP (Ozarda et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…MOM cytokines and their potential effect on the infant are a relatively new area of research. The presence of both pro- and anti-inflammatory cytokines in MOM suggests specific biologic roles that remain to be elucidated, and limited studies suggest a potential association with infant outcomes ( Baumgartel et al, 2016 ). Although limited research has focused on term infants, MOM cytokines appear to change over time and vary by term versus preterm delivery ( Baumgartel et al, 2016 ; Chollet-Hinton et al, 2014 ; Groer et al, 2014 ; Ustundag et al, 2005 ) and by geographic or socioeconomic setting ( Ruiz et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation